New threats and countermeasures in digital crime and cyber terrorism - Dawson, Maurice, 1982-; Omar, Marwan, 1982- (Advances in digital crime, forensics, and cyber terrorism (ADCFCT) book series., 2015)
"This book brings together research-based chapters and case studies on security techniques and current methods being used to identify and overcome technological vulnerabilities with an emphasis on security issues in mobile computing and online activities"--